TANGGUNG JAWAB PEMERINTAH DALAM MEMBENTUK PERATURAN PELAKSANA YANG DIDELEGASIKAN OLEH UNDANG-UNDANG DITINJAU DALAM PERSPEKTIF KEPASTIAN HUKUM - Silaban, Dessy Fransiska Br.; Firdaus, Firdaus; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Government regulations are regulations that make the provisions of a law work or be treated. In other words, government regulations are the implementing regulations of law. Implementing regulations are regulations that are located under the law which function to administer the provisions of the law. Implementing regulations originate from the authority of the delegation, the delegation of authority in the formation of statutory regulations is the delegation of authority to form laws and regulations carried out by higher statutory regulations to lower legislations The main problem is that laws delegate the formation of government regulations as implementing regulations of laws, but with a long period of time the government has not yet established and issued government regulations. Government policies are considered to be able to be demanded to establish and issue government regulations in a timely manner according to the time period determined by law so that there is no legal vacuum in the implementation of a rule, the demands of this government policy as a benchmark for the government to be responsible for issuing government regulations for guarantee legal certainty, that the law is carried out, that those who are entitled according to law can obtain their rights and that decisions can be enforced. The implementation of the law is in accordance with the sound so that the community can ensure that the law is implemented.The objectives of this study are: First, to determine the government's responsibility in forming implementing regulations delegated by law in terms of legal certainty, Second, to determine the urgency of implementing regulations delegated by law in terms of legal certainty. This type of research is normative legal research or literature law research using research methods on legal principles.From the research, there are two main points that can be concluded. First, the central government is responsible for establishing and issuing government regulations as implementing regulations that are delegated by law, namely that the government is required to carry out government tasks according to its authority. Every use of authority by the government is always accompanied by responsibility in accordance with the principle of no authority without accountability. Second, the urgency of government regulations as implementing regulations of the consistency of delegation by law is to ensure that there is a line of legal certainty, that the law can be effective and the public can ensure that the law is implemented according to its articles.Keywords: Responsibility - Implementing Regulations - Legal Certainty